Pelindungan Hukum Atas Potensi Indikasi Geografis Di Kabupaten Tapanuli Utara - Balqis Siagian; O.K Saidin; Suhaidi Suhaidi; Sunarmi Sunarmi (Iuris Studia: Jurnal Kajian Hukum, 2021)
Geographical indications are Indonesia's national economic potential that can provide commercial added value to products due to their originality and product limitations that cannot be produced in other areas. North Tapanuli Regency, as an area that has the potential of Geographical Indications must immediately register the products that are geographically indicated to be registered immediately so that they are not used by other parties who are not entitled to and receive legal protection. The problems of this thesis are: how are the characteristics of products that have the potential as Geographical Indications to be registered for geographical indications in North Tapanuli Regency, what obstacles are faced in registering products that have the potential as geographical indications in North Tapanuli Regency and what is the role of the Regional Government in registering agricultural products that are potential as a geographical indication in North Tapanuli Regency. This type of research is empirical juridical where the data sources are obtained from primary legal materials, secondary legal materials and tertiary legal materials. The data was collected through library research and field studies by conducting interviews. The data analysis used is qualitative data analysis. Based on the results of the study, it was concluded that the characteristics of products that have the potential as GIs to be registered for geographical indications in North Tapanuli Regency are to meet objective requirements, namely elements that indicate reputation, quality, and characteristics that must be shown through a product with potential GIs and subjective requirements, namely the parties. those who can apply for registration of GIs are the Provincial or Regency/Municipal Governments and parties who are operating goods that have such GIs. The obstacles faced in the registration of agricultural products that have the potential as geographical indications in North Tapanuli Regency are: lack of information from the government, low legal awareness and understanding of the community and the length of the IPR registration process. The role of the Regional Government in registering agricultural products that have the potential as geographical indications in North Tapanuli Regency is still not focused and less serious. For this reason, it is suggested to the community to be enthusiastic and participate in the socialization of IGs, the community must cooperate with the Regional Government in registering IGs and the Regional Government is expected to play a more active role in socializing the importance of protecting IPR